Conceptual Framework to Improve Carbon Performance via Carbon Strategies and Carbon Accounting - KASBUN, Nur Fatin; ONG, Tze San; MUHAMAD, Haslinah; SAID, Ridzwana Mohd (Journal of Environmental Management and Tourism, 2020)
Rapid transformation from agriculture to industrialized economy in Malaysia has evidently attributed to the accelerated increase in carbon emissions. Carbon emission growth that led to climate change is a very complex spectacle and that is when carbon accounting has emerged. The emergence of carbon accounting has assisted and motivates organizations in achieving their carbon reduction objectives because the system is considered essential in combating climate change. Despite that, the accounting methodology used for climate change remains poorly understood in the current business sphere. As such, it is argued that if carbon strategy is deliberated properly by an organization, carbon accounting will effectively outlines the effects on carbon performance. Enhancing profits is the focal point, but the focus on the sustainable development of the business in the future is crucial. This paper discusses interlinks of corporate carbon strategies, carbon accounting and carbon performance of organizations in Malaysia.